The Risk of Bullying as a Result of COVID-19 among University Students - Alrawashda, Maissa Nasser (Opción)
This Article is aimed to reveal the types and levels of bullying to which undergraduate Asian students are exposed to because of the COVID-19 pandemic. By applying the Multidimensional Bullying Victimization Scale to (202) students of Asian nationalities (Indonesian, Uzbek, Thai, Filipino, Chinese) who are pursuing their university education in Governmental universities. The results found that Asian male and female students have encountered four types of bullying: Relational Bullying, Cyber Bullying, Physical Bullying and Race and Culture-based Bullying. Cyber bullying was the most common type of bullying among students. The results also revealed that the Chinese students are the students who faced most bullying, followed by the Indonesian students, respectively, while the Filipino students are the students experience the least bullying as a result of the COVID-19 pandemic.